2014
DOI: 10.3748/wjg.v20.i21.6632
|View full text |Cite
|
Sign up to set email alerts
|

Potential role of human papilloma virus in the pathogenesis of gastric cancer

Abstract: The study does not confirm the presence or biological activity of HPV in tumor tissues. Thus, the relationship between GAC and HPV infection, in the Central European population seems doubtful.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 0 publications
1
18
0
Order By: Relevance
“…The same relationship with the p53 , p21 ,17,24,26,40 and p16 18,35,37 genes was reported to found with HPV prevalence. Some studies have found that HPV could coinfect with H .…”
Section: Discussionsupporting
confidence: 79%
“…The same relationship with the p53 , p21 ,17,24,26,40 and p16 18,35,37 genes was reported to found with HPV prevalence. Some studies have found that HPV could coinfect with H .…”
Section: Discussionsupporting
confidence: 79%
“…In this review, we will focus on the role of gastrin in the etiology of gastric cancer and at the same time give an explanation of the decline in frequency. We will only cover cancers originating from epithelial cells (carcinomas) and will not discuss the importance of Epstein–Barr virus that plays a role neither in gastric carcinogenesis (6) nor in human papilloma virus, which has a less established impact (7). …”
mentioning
confidence: 99%
“…Infections hijack the host DNA methylation mechanism via increasing DNMTs in order to control host transcription to their benefit. cancer, suggesting its potential role as risk factor for gastric cancer [106][107]. Study on human cervical carcinoma SiHa and CaSki cell lines has shown that P53 TSG suppresses DNMT1 expression [108].…”
Section: Expression Of Dnmts and Susceptibility To Infections In Gastmentioning
confidence: 99%